Knockdown ATG5 gene by rAAV9 alleviates doxorubicin-induced cardiac toxicity by inhibiting GATA4 autophagic degradation - Ai-Li Xu; Zheng Shen; Shi-Hao Wang; Hai-Yun Luan; Yong Xu; Ze-Chun Kang; Zi-Qi Liao; Jie Liu; Xiao-Lei Duan; Wei-Hua Bian; Hui Sun; Xin Xie (Frontiers in Pharmacology)
Doxorubicin (DOX) is a prevalent chemotherapeutic drug for treating several malignancies. However, the mechanisms of DOX induced cardiac toxicity is not fully understood. Previous studies have demonstrated that autophagy activation is essential in DOX-induced cardiac toxicity. Nevertheless, studies on the role of autophagy protein 5 (ATG5) in DOX-induced cardiac toxicity remain limited. Therefore, this study aimed to investigate the role of ATG5 in DOX-induced cardiac toxicity. Mice were intravenously administered DOX (5 mg/kg) for 4 weeks to establish a cardiac toxicity model. Heart function was determined using echocardiography, and cardiac tissue was assessed for protein expression, mRNA levels, fibrosis, and immunofluorescent staining. DOX treatment upregulated autophagy-related gene expression but inhibited autophagic flux in vitro and in vivo. DOX–treated mice exhibited decreased heart function and cardiomyocyte size and increased cardiac fibrosis, oxidative stress, and apoptosis. These effects of DOX were partially alleviated by rAAV9 expressing shRNA-ATG5 and deteriorated by rAAV9-ATG5. We demonstrated that genetic ATG5 knockdown or autophagy inhibition by chemical inhibitors increased GATA4 protein expression, which was reduced by ATG5 overexpression or autophagy activator in vitro and in vivo, suggesting that ATG5-mediated autophagy promoted GATA4 degradation. Moreover, enforced GATA4 re-expression significantly counteracted the toxic effects of ATG5 on DOX-treated hearts. In conclusion, our study demonstrated that manipulating ATG5 expression to regulate GATA4 degradation in the heart may be a promising approach for DOX-induced cardiac toxicity.